EDUCAŢIA PROSPECTIVĂ - DIMENSIUNE A EVOLUŢIEI ŞI PROGRESULUI - USM ADMIN (Moldova State University, 2008)
Generally in the circumstances of a fast development of knowledge and of society, a lot of practices and knowledge which are available nowadays, in the future it will be exceeded, obsolete. The future creates requirements more and higher, but the education needs to develop them, to develop a prospective character which is strategically superior to the actual education. Such requirements imply enormous changes in the skills of teaching, organizing systematically activities which will help the pupil to define, to explain and to verify their values. But it is not enough to orient this system to the future because it is necessary also to change the attitude of the individual towards the time of the foreseeing of the acti- vities in diverse life conditions, as well as the formation of a pliant behaviour, which will be adaptable to the new social and economic conditions.